Contribution of multiple intelligences and self-regulated learning to students’ HOTS in junior high school - Kusumaningsih, Novia; Torro, Supriadi; Najamuddin (Jurnal Teori dan Praksis Pembelajaran IPS, 2025)
In helping to answer various very complex challenges in life in the 21st century, higher-order thinking skills (HOTS) in social studies learning are vital. Multiple intelligences (MI) and self-regulated learning (SLR) play an active role in shaping the creativity of HOTS mastery. Therefore, the essence of this study is designed to investigate the relationship between MI and SLR on students’ HOTS abilities, especially in social studies learning. This study chose a quantitative approach with Structural Equation Modeling (SEM) and Partial Least Squares (PLS) techniques analyzed using SmartPLS 3 software. A total of 465 students at the junior high school level were selected as respondents in this study. The number of responses was selected using a multilevel sampling technique. This study used a questionnaire with a Likert scale to explore MI, SRL, and student learning motivation, and used a multiple-choice test to measure their HOTS abilities in social studies learning. The results of the study answered that there was a significant impact, both directly and indirectly, from MI and SRL on students’ HOTS abilities in social sciences, with learning motivation as an intermediary variable. Further findings also revealed that female students’ SRL showed a stronger influence on learning motivation compared to male students. The influence of SRL also had a broader impact on learning motivation in children who lived with their parents compared to those who did not. This study concluded that learning motivation is the main key for students in developing learning cognitive skills and strengthening their independence.